The Impact of Work–Life Balance, Job Stress, and Compensation on Employee Retention - Niken Widyastuti; Jemadi; Lisa Gresti Sella Damanik; Noorhani Dyani Laksmi (Journal Management & Economics Review (JUMPER), 2026)
Employee retention has become an important issue for organizations seeking to maintain workforce stability and sustain long-term organizational performance. This study aims to examine the impact of work–life balance, job stress, and compensation on employee retention. A quantitative research approach was employed using a survey method to collect primary data from 150 employees working in various organizations. The data were analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS. The results indicate that work–life balance has a positive and significant effect on employee retention, suggesting that employees who are able to maintain a balance between work and personal life are more likely to remain committed to their organizations. In contrast, job stress has a negative and significant influence on employee retention, indicating that higher levels of workplace stress increase the likelihood of employee turnover. Furthermore, compensation was found to have the strongest positive effect on employee retention, demonstrating that fair and competitive compensation plays a crucial role in motivating employees to stay within the organization. These findings highlight the importance of implementing effective human resource management strategies that promote work–life balance, reduce job stress, and provide competitive compensation systems. By addressing these factors, organizations can improve employee satisfaction, strengthen organizational commitment, and enhance employee retention in the long term.Work–Life Balance